Optimization Strategy for the Use of Instagram Reels Feature to Increase Consumer Interest and Competitiveness in Star Clown MSMEs in Kediri City - Wulandari, Anggi Marta; Bhirawa, Sigit Wisnu Setya; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research Objectives : The purpose of this research is to optimize the digital marketing mix by utilizing the Instagram reels feature to increase consumer interest and competitiveness in Star Clown MSMEs in Kediri City. Design/Method/Approach : The descriptive qualitative method uses data source triangulation techniques with a phenomological approach, conducting interviews with 4 informants according to the recommendation criteria from the owner of Star Clown MSMEs. Research Findings : The results of this study Star Clown MSMEs face challenges in marketing, by using the latest digital marketing with Instagram social media that focuses on the reels feature to be effective access in the current era. This study shows that the impact of MSME development is very influential in identifying the extent to which the use of marketing mix can optimize digital marketing, attract consumer attentio and increase competitiveness to reach a wider market. Theoretical Contribution / Originality : This study is expected to provide additional information for business actors who are still using traditional marketing and provide an overview so that they can develop their business by raising the level of digital marketing strategies of interest and can increase competitiveness in business. Practitioner / Policy Implications : This research is expected to provide input in the form of information suggestions for MSME owners regarding the use of Instagram social media digital technology to increase consumer interest and competitiveness. For readers, this research is expected to be an additional reference regarding the mix of digital marketing strategies through Instagram for MSMEs. Research limitations : In this study, there is a lack of detailed and detailed data information, because actors of Star Clown MSMEs in Kediri City do not do bookkeeping regularly.